2010
DOI: 10.1007/s10499-010-9384-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of primers and a procedure for specific identification of the diatom Thalassiosira weissflogii

Abstract: A recent study showed Thalassiosira weissflogii to be a diatom containing suitable nutrition for larviculture of the black tiger shrimp, Penaeus monodon. Accurate and practical identification of this diatom species is therefore important for commercial hatcheries. The purpose of this study was to establish a DNA-based method of identification to supplement morphological examination, avoiding confusion with other Thalassiosira sp. Primers, 18SF/28SR1, specific for ribosomal DNA genes (3 0 -end of 18S rDNA throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We question the taxonomic identity of the strain classified as T. oceanica CCMP1616, after the petF gene failed to amplify with the primers used for the other T. oceanica strains ( Figure 2 ). The classification of this strain with the well-established eukaryotic barcoding region ITS2 ( Supplementary Figure S2 ; Coleman, 2003 , 2009 ; Sorhannus et al, 2010 ; Caisova et al, 2011 ; Senapin et al, 2011 ; Whittaker et al, 2012 ) showed that CCMP1616 is unlikely to belong to the T. oceanica species because it is not part of the highly supported monophyletic T. oceanica clade. The 18S phylogeny further indicates that it instead stands as an independent neighbor of the other Thalassiosira clades, which cluster well according to their assigned species ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…We question the taxonomic identity of the strain classified as T. oceanica CCMP1616, after the petF gene failed to amplify with the primers used for the other T. oceanica strains ( Figure 2 ). The classification of this strain with the well-established eukaryotic barcoding region ITS2 ( Supplementary Figure S2 ; Coleman, 2003 , 2009 ; Sorhannus et al, 2010 ; Caisova et al, 2011 ; Senapin et al, 2011 ; Whittaker et al, 2012 ) showed that CCMP1616 is unlikely to belong to the T. oceanica species because it is not part of the highly supported monophyletic T. oceanica clade. The 18S phylogeny further indicates that it instead stands as an independent neighbor of the other Thalassiosira clades, which cluster well according to their assigned species ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Class-specific and genus-specific primers are generally designed to target the mature ribosomal RNA gene sequences of 16S, 23S, 18S, 5.8S, or 28S, which are considered to be large in size and highly conserved. In addition, internal transcribed sequences (ITS) that are more divergent are also used for species or strain identification [ 41 ]. In the present study, Oligonucleotide primers were utilized to amplify the 18S rDNA, 16Sr DNA, 5.8S, and rbcl genes of the tested microalgae ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Primers, ITS1-F (5′CCGTAGGTGAACGTGCGGAAGGATC3′), (5′CGTATCGCATTTCGCTGCGTTCTTC3′) ITS1-R, were designed in this study. The polymerase chain reaction was conducted using 25 µL reaction mixtures composed of 1.0 µL of the first PCR product, 0.5 µL of 10 µL MdNTPs, 0.5 µL of 10 µM of each primer, and 0.25 µL of Taq DNA polymerase (5 units/µL, Invitrogen, Waltham, MA, USA), 0.5 µL of 50 mM MgCl2, 2.5 µL of 10 × PCR buffer, and 19.25× of ultra-pure distilled water according to the protocol [46]. Subsequently, the PCR products underwent purification through a Qiagen PCR kit and were sequenced by BGI Biotechnology (BGI, Shenzhen, China).…”
Section: Species Identificationmentioning
confidence: 99%
“…In conducting the phylogenetic study, we retrieved the Internal Transcribed Spacer regions of C. meneghiniana and related sequences from the NCBI database and discovered that the ITS gene sequences in this study were highly similar (100%) to Cyclotella meneghiniana BIMS-PP0014 [46]. A phylogram with closely related species constructed using ITS1 sequences of Cyclotella meneghiniana (Stephanocyclus meneghinianus) is shown in Figure S1.…”
Section: Molecular Identification Of C Meneghinianamentioning
confidence: 99%